2007
DOI: 10.1111/j.1540-8175.2007.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Congenital Anomaly: Biatrial Appendage Aneurysm with Atrial and Ventricular Septal Defect

Abstract: Atrial appendage aneurysms are extremely rare entities in cardiology practice. There are reports of solitary left and right atrial appendage aneurysms in the literature. A case of biatrial appendages aneurysms is reported here. This is the first report of such an anomaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 8 publications
0
25
0
2
Order By: Relevance
“…In this review of 17 reported cases males outnumber the females. 6,7 Endocardial fibrosis is a common histological finding and lipomatous degeneration of the RAAA without evidence of inflammatory reaction may be seen. It has been diagnosed in neonates and even during prenatal period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review of 17 reported cases males outnumber the females. 6,7 Endocardial fibrosis is a common histological finding and lipomatous degeneration of the RAAA without evidence of inflammatory reaction may be seen. It has been diagnosed in neonates and even during prenatal period.…”
Section: Resultsmentioning
confidence: 99%
“…CT angiography and MRI are excellent adjuvant imaging tools, in patients in whom the diagnosis is not clear on TEE, with high sensitivity and specificity. 3,6,9,10 Periodic monitoring of RAAA in asymptomatic patients with cardiac MRI or CT for evidence of enlarging RAAA has been shown to be a useful tool in selecting patients for early surgical intervention. 2 A 24-hour Holter recording should be requested in patients complaining of palpitations and/or normal ECG for the evaluation of atrial tachyarrhythmias.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven (15%) did not undergo surgery (5 refused surgery, 5-9 2 with no arrhythmia or thrombus, 2 reasons not mentioned, 1 autopsy diagnosis, and 1 had bilateral atrial appendage aneurysm and ASD/VSD with Eisenmenger's syndrome 10 ). These patients were treated conservatively with anticoagulants for either presence of thromboembolic complications or for prophylaxis.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Approximately 100 cases of right atrium abnormalities have been reported in the literature 1 . Giant RAA is a very rare anomaly discovered accidentally by an enlarged silhouette on a chest x‐ray; an associated atrial septal defect has been reported 2,3 . Slightly less than half of the cases have symptomatic arrhythmias.…”
mentioning
confidence: 99%
“…1 Giant RAA is a very rare anomaly discovered accidentally by an enlarged silhouette on a chest x-ray; an associated atrial septal defect has been reported. 2,3 Slightly less than half of the cases have symptomatic arrhythmias. The optimal treatment is controversial; a conservative approach is recommended in the absence of symptoms, leaving surgical treatment to symptomatic cases.…”
mentioning
confidence: 99%